Lexical Profile of Newspapers Revisited: A Corpus-Based Analysis - Ha, Hung Tan (Frontiers in Psychology, 2022)
The present study analyzed the vocabulary profile of the News on the Web (NOW) corpus, which contained 12 billion words from online newspapers and magazines in 20 countries to determine the vocabulary knowledge needed to reasonably understand online newspaper and magazine articles. The results showed that, in general, knowledge of the most frequent 4,000 word families in the British National Corpus/Corpus of Contemporary American English (BNC/COCA) wordlist plus proper nouns, marginal words, transparent compounds and acronyms was necessary to gain 95% coverage for the NOW corpus. However, when it came to the 98% coverage, online newspaper and magazine articles from different countries had relatively distinct lexical demands. In-depth analyses were carried out and the findings offered comprehensive insights into the issue. Implications for teaching and learning were also provided.